2008
DOI: 10.1017/s0008423908080426
|View full text |Cite
|
Sign up to set email alerts
|

Media, Public Opinion and Health Care in Canada: How the Media Affect “The Way Things Are”

Abstract: Abstract.Health care has arguably been the most important issue in Canadian politics in the past decade. This paper focuses on the extent to which the media affect public perceptions of “the way things are” in the Canadian health care system. Individual perceptions of the state of health care are analyzed as being a function of personal experience with the system, loyalty or pre-formed opinions and the information that the individual receives through the media. Results indicate that media use has a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…While satisfaction is understandably more related to individuals' personal experiences with the health system (Wendt et al ), the normative preference for state involvement may be shaped by the level of people's satisfaction with the system. Blidook () has noted that the formation of public attitudes towards health policy is determined by a combination of pre‐formed opinions, information received externally and personal experiences. Soroka et al .…”
Section: Theoretical Backgroundcontrasting
confidence: 87%
“…While satisfaction is understandably more related to individuals' personal experiences with the health system (Wendt et al ), the normative preference for state involvement may be shaped by the level of people's satisfaction with the system. Blidook () has noted that the formation of public attitudes towards health policy is determined by a combination of pre‐formed opinions, information received externally and personal experiences. Soroka et al .…”
Section: Theoretical Backgroundcontrasting
confidence: 87%
“…In part, this relates to the question of whether and to what extent individuals formulate opinions and make decisions in a health care setting on the basis of personal experience versus pre-formed opinions due to ideology or other informational sources. Prior work by Blidook suggest opinions on health care derive from multiple sources (Blidook 2008). Importantly, the literature suggests that the more directly a person experiences an issue, the less open he or she is open to external influences (e.g., via the media) on that issue (Mutz 1992; Ball-Rokeach and DeFleur 1976; Blidook 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Prior work by Blidook suggest opinions on health care derive from multiple sources (Blidook 2008). Importantly, the literature suggests that the more directly a person experiences an issue, the less open he or she is open to external influences (e.g., via the media) on that issue (Mutz 1992; Ball-Rokeach and DeFleur 1976; Blidook 2008). Thus, the content of advertising matters not only for policy (i.e., the composition of the individual Marketplace and the types of appeals used by advertisement sponsors) but also for politics, particularly what information about the ACA the general public observing these marketing efforts might draw in forming their attitudes about the law, efforts to replace or modify it, and future health reform efforts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in regards to the primary focus of media studies, the majority of past research has addressed media representations of body images, particular diseases, the uptake of health care and coverage of pharmaceuticals (Hayes et al 2007). Research has identified that public perceptions and preferences are altered based on the media framing of issues, especially war coverage (Blidook 2008). In terms of the reporting on genetics, the degrees and sources of inaccuracies have been investigated, as well as the general weaknesses of the media's coverage of medical breakthroughs (Bubela & Caulfleld 2004).…”
Section: Past Researchmentioning
confidence: 99%
“…More specifically, the media have a significant impact upon perceptions of health care (Blidook 2008). Recent research has shown that public opinion and public perceptions of policy issues play an important role in policy change.…”
Section: Theoriesmentioning
confidence: 99%